Hierarchically porous Co-N-C electrocatalysts with enhanced mass transport and cobalt utilization efficiency for oxygen reduction reaction in high-performance PEMFCs - Baek, Jinhyuk; Son, Hyeonwook; Lee, Eungjun; Yoo, Sung Jong; Kim, Moonsu; Lee, Gibaek (Royal Society of Chemistry, 2025)
Cobalt-coordinated nitrogen-doped carbon (Co-N-C) materials have emerged as promising alternatives to platinum-based catalysts for proton exchange membrane fuel cells (PEMFCs) due to their cost-effectiveness and durability. However, conventional Co-N-C catalysts exhibit limitations in mass transport as the active Co-Nx sites are often embedded within a dense carbon matrix, reducing their site accessibility. This study introduces a melamine-assisted synthesis approach to develop Co-N-C catalysts with a hierarchical porous structure that significantly enhances the accessibility of Co-Nx active sites. By incorporating melamine with zeolitic imidazolate frameworks (ZIFs) during synthesis, an optimized pore architecture is achieved, facilitating efficient mass transport of reactants (H+ and O2) to active sites and enabling effective water removal. This unique structure yields a high density of accessible active sites, resulting in superior oxygen reduction reaction (ORR) activity. XPS and electrochemical measurements confirm the increased density of Co-Nx species, establishing a robust structure-property correlation. In membrane electrode assembly (MEA) integration for PEMFC applications, the synthesized Co-N-C catalyst exhibits excellent performance with enhanced stability and reduced mass transfer overpotential. This work highlights a scalable strategy for developing durable, highly active non-precious metal catalysts, advancing the practical viability of PEMFC technology.